Ankle Brakhial Indext (ABI): a tools for detect peripheral arterial disease (PAD) - Wahyuni, Riska; Khasanah, Nopi Nur; Amal, Ahmad Ikhlasul (Media Keperawatan Indonesia, 2024)
Peripheral Arterial Disease (PAD) is a common complication among patients with type 2 diabetes mellitus, characterized by atherosclerosis that leads to the narrowing of the arteries in the legs and feet. PAD complications include pain, neuropathy, and potential limb amputation. This study reviews the effectiveness of the Ankle-Brachial Index (ABI) as a diagnostic tool for PAD detection in diabetic patients. A literature review was conducted, sourcing 266 articles from PubMed, Google Scholar, and ScienceDirect databases within the 2019-2024 period; six articles met the inclusion criteria. The analysis indicates that ABI is a sensitive and accurate diagnostic method, particularly for patients with an ABI <0.9 who are at higher risk of cardiovascular complications. PAD risk factors include older age, hypertension, and smoking. ABI also shows high concordance with Doppler Ultrasonography (DUS) for various degrees of arterial stenosis. In conclusion, ABI is a reliable, non-invasive diagnostic tool for early PAD detection in diabetic patients. Routine use of ABI in screening programs may help prevent further complications through early diagnosis and intervention, especially for patients with diabetes mellitus.